Feasibility study of a new injection method for EMI reduction in indoor broadband PLC networks - Pang, T. S. (2013)
This paper proposes a new signal-injection technique which utilizes the earth wire that is present in the electrical system to reduce electromagnetic-interference (EMI) radiation from indoor broadband power-line communication (PLC) networks. The new signal injection method is compared with the typical signal injection technique used in PLC modems today. The method is also compared with an alternative signal-injection technique proposed by other researchers. For a balanced network, the proposed new signal-injection technique allows for a significant reduction in the level of radiated electric field of up to 40 dB in the frequency range from 1 to 30 MHz when compared to the typical signal-injection technique. The feasibility and practicality of using the new signal-injection technique for the reduction of EMI radiation are discussed.